Uganda coffee agronomy training: Impact evaluation report - Hoffmann, Vivian; Murphy, Mike; Harigaya, Tomoko (International Food Policy Research Institute, 2024)
This report describes the methods and findings of a randomized controlled trial evaluating the impact of coffee agronomy training and phone-based advisory services on farmer practices and observed coffee yield. In-person training was provided in randomly selected villages over the course of two years by Hanns R. Neuman Stiftung (HRNS) and TechnoServe in two separate regions of Western Uganda encompassing six districts. Messages reinforcing this training were sent to a subset of farmers in villages where training was offered by Precision Development (PxD), and standalone messages were sent to a subset of farmers in villages where no training was offered. The program period spanned the onset of the COVID-19 pandemic and associated lockdowns, which significantly affected how training could be delivered and likely reduced its impact.